Admired and disgusted? Third parties’ paradoxical emotional reactions and behavioral consequences towards others’ unethical pro‐organizational behavior - Tang, Pok Man; Yam, Kai Chi; Koopman, Joel; Ilies, Remus (Personnel psychology, 2022)
Unethical pro‐organizational behavior (UPB) is often visible to co‐workers; however, reactions to UPB are rarely considered in empirical research in spite of their importance to the social dynamics in the workplace. Drawing upon appraisal theory of emotion and the behavioral ethics literature, we predict that observing UPB would lead third parties to experience admiration due to the pro‐organizational nature of UPB; these third parties would in turn be motivated to display more helping behavior towards the UPB actor. Conversely, we predict that observing UPB would lead third parties to experience disgust due to the unethical nature of UPB; these third parties would dis‐identify themselves from the UPB actor by instigating incivility. Meanwhile, they would disengage themselves from the UPB actor by avoiding them in subsequent interactions. In addition, the observing employees might also engage in action‐oriented behavior such as whistle‐blowing behavior to sanction the UPB actor. Across an experience‐sampling study with three daily assessments as well as an experimental study, we find support for these predictions. Furthermore, we find that third parties’ moral attentiveness moderates the link between observed UPB and disgust, such that observed UPB leads to heightened feelings of disgust only when third parties have high levels of moral attentiveness. We conclude by discussing the theoretical and practical implications of our work.